WEBSITE-BASED POPULATION ADMINISTRATION SERVICE INFORMATION SYSTEM FOR URBAN VILLAGE - Dwi Roro Pangestu; Muh. Nanang Wiraalifuddin; Nining Suharyanti (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Population administration services in Pesanggrahan Village are currently still carried out manually, requiring residents to submit physical documents, thus triggering queues and risking document loss. This research aims to design and build a website-based Population Administration Service Information System to digitize the correspondence process, integrate automatic notification features, and publicize regional potential such as MSMEs and tourism. Software development uses the Waterfall method, which includes needs analysis, system design, implementation, testing, and maintenance, built using the Laravel framework and MySQL database. The research results in an integrated platform that facilitates residents to submit letter requests online and upload required digital documents, effectively cutting the physical bureaucratic chain. This system is equipped with Simple Mail Transfer Protocol (SMTP) automation that sends automatic approval notifications via email. Functional testing using Black Box Testing demonstrates that all features function validly and as expected. Conclusively, the implementation of this system successfully optimizes bureaucratic efficiency, secures archival records, and increases the visibility of regional potential.